1984
DOI: 10.1111/j.1365-246x.1984.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

The long-period electromagnetic response of the Earth

Abstract: The techniques of complex demodulation and spherical harmonic analysis have been used to examine the time-, frequency-and locationdependent properties of the long-period electromagnetic response of the Earth. Fourteen years of daily, three component magnetic field data, recorded by 18 permanent geomagnetic observatories, were used to estimate the response in the period range 2-200 day. It is found that lateral conductivity inhomogeneities within the Earth, notably the oceans, have a considerable effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…BANKS (1969) fit 4 stations to P° geometry, but once this geometry is assumed a response can be found for each single observatory. This was done for 17 stations by ROBERTS (1984) and 22 stations by SCHULTZ and LARSEN (1987 (taking the ratio of the coherent parts of the horizontal and vertical field spectra) produced poor results. Roberts used complex demodulation to compensate for time-variations in sourcefield strength, while Schultz and Larsen used a robust analysis and the smooth power series expansion method of LARSEN (1980) to compute response functions.…”
Section: Geomagnetic Response Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…BANKS (1969) fit 4 stations to P° geometry, but once this geometry is assumed a response can be found for each single observatory. This was done for 17 stations by ROBERTS (1984) and 22 stations by SCHULTZ and LARSEN (1987 (taking the ratio of the coherent parts of the horizontal and vertical field spectra) produced poor results. Roberts used complex demodulation to compensate for time-variations in sourcefield strength, while Schultz and Larsen used a robust analysis and the smooth power series expansion method of LARSEN (1980) to compute response functions.…”
Section: Geomagnetic Response Functionsmentioning
confidence: 99%
“…At the longest periods, data errors are larger and do a better job of representing inter-station scatter, and so it is likely that at least some of the increased variance at long periods is due to uncertainty in response function estimation. ROBERTS (1984) considered variations between stations to be caused by induction in the world ocean, while SCHULTZ and LARSEN (1990) inferred lateral variation in mantle conductivity . There is little doubt that both these phenomena contribute to the observed variations between stations, and both ideas are consistent with increased variation at shorter periods .…”
Section: A Global Response Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are caused by localized active regions on the Sun's surface and semi-persistent emission of high-speed streams of solar plasma -together they modulate geomagnetic activity. Since the Sun is not a solid body, it does not have a discrete rotational frequency (Howard, 1984), and so many peaks corresponding to periods of approximately one month are seen in the geomagnetic spectrum (Roberts, 1984). As far as we are concerned, this type of geomagnetic activity is not solar-quiet variation -it is disturbance -and we have not removed it from the Dist time series.…”
Section: Examination Of Local Magnetic Disturbancementioning
confidence: 99%
“…Achache et al (1981) claimed that a model proposed by Ducruix et al (1980) is better than that of Banks, comparing the response functions computed for respective models. Constable (1993) took an average of response functions obtained by Roberts (1984) and Schultz and Larsen (1987), at periods between 10 5 -10 7 seconds (8.64 × 10 −3 ∼ 8.64 × 10 −1 cycle/day), and estimated the electrical conductivity structure of the mantle. McLeod (1994) obtained a response function for periods ranging from 2 months (∼1.64 × 10 −2 cycle/day) to 2 years (∼1.37 × 10 −3 cycle/day) and found that it is consistent with an electrical conductivity model which indicates a conductivity value of about 10 S/m at the core-mantle boundary.…”
Section: Introductionmentioning
confidence: 99%